Quality Assesment of The Kerinci District Social Services Website Using The Webqual 4.0 Model - Fadhly, Syaifullah; Putra, Yeffry Handoko (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
The Kerinci Regency Social Service is a local government agency tasked with administering social welfare programs and community assistance. Its official website serves as a central public information platform and a channel for interaction between citizens and the local government. However, in practice, this platform still faces several shortcomings, including incomplete or outdated information, inaccessible features, and the lack of an active public complaints service. Therefore, this study aims to assess the quality of the Kerinci Regency Social Service website using the WebQual 4.0 framework, which focuses on three main dimensions: usability, information quality, and interaction quality and their impact on user satisfaction. A quantitative research design was employed, with data collected through an online questionnaire distributed to active users of the Kerinci Regency Social Service website. User responses were analyzed using multiple linear regression with SPSS 26. This study found that usability (coefficient = 3.633) and interaction quality (coefficient = 2.365) have a significant positive influence on user satisfaction. In contrast, information quality (coefficient = –0.687) showed no significant effect. These results suggest that ease of navigation and the quality of service interactions play a greater role in shaping user satisfaction than the completeness of the information provided. Based on these insights, website administrators are advised to prioritize improving usability and user interaction features to enhance overall service quality.